Analytical Validation of Quantitative High-Performance Liquid Chromatographic Methods in Pharmaceutical Analysis: A Practical Approach - Bonfilio, Rudy [UNESP]; Laignier Cazedey, Edith Cristina [UNESP]; de Araujo, Magali Benjamim; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis Inc, 2012)
Analytical validation is an essential component in allowing a laboratory to ensure routine acceptable performance of analytical methods. Despite the considerable amount of important published work on this subject, diversity still prevails in the employed methodologies because validation of an analytical method depends on the specific purpose of that method. This can lead to difficulties in validation approaches and the interpretation of results. Aiming to assist in the planning of validation methods, we discuss relevant approaches of various parameters in quantitative high-performance liquid chromatographic methods and validation fields in pharmaceutical analysis. Moreover, this article provides several up-to-date examples that should be useful as an introduction to analytical validation for practical applications in academic research or the industrial sector.
Keywords: analytical method validation; quality control; high-performance liquid chromatographic methods; pharmaceutical analysis